RANCANG BANGUN APLIKASI PENDATAAN PENDUDUK BERBASIS WEB DI KELURAHAN BUGIS - Eri Sasmita Susanto; Herfandi; Mujahidin Patti Peiloh (Program Studi Informatika Universitas Teknologi Sumbawa, 2021)
Population data collection is intended to increase efficiency in terms of community services. So far, Bugis Village, Sumbawa Regency, still has a system that has not been computerized, making it difficult and slow in the processing of population data. Therefore, it is necessary to conduct research to build data processing applications. The purpose of processing this data is to make it easy for employees to provide efficiency in community service. In this implementation, the programming language PHP and MySQL are used as the database. Data collection methods used in this research are interview, observation, documentation and literature study methods as well as software development methods using the waterfall method. The test method in this study uses black-box testing which is done to test the software in terms of functional specifications.